PJMHS 2021
DOI: 10.53350/pjmhs2115103103
|View full text |Cite
|
Sign up to set email alerts
|

Brief Motivational Interviewing Counseling to Improve Oral Hygiene Behavior Among Adolescent

Abstract: Aim: To analyze the effect of the brief motivational interviewing counselling approach on the knowledge, attitudes and tooth brushing practice of adolescents. Method: This research is a quasi-experiment with a pre-test and post-test design with a control group design. The research sample was 80 adolescents aged 12 and 13 years. Respondents were divided into two groups, namely 40 intervention and control groups based on inclusion criteria. The intervention group was given the MI approach, and the control group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(28 reference statements)
0
3
0
1
Order By: Relevance
“…This technique is often used in Dutch general dental practice to enhance patients' intrinsic motivation for adhering to oral‐health‐promoting behaviours (Gresnigt‐Bekker, 2011). The OHPs in our study also indicated using this technique, although its effectiveness in oral healthcare has not yet been confirmed (Carra et al, 2020; Gao et al, 2014; Ulliana et al, 2021). In addition, it should be noted that there are various ways in which MI should be tailored to the special needs of those with MBID, such as adapting the language, summarising frequently, and using visual aids and role‐play (Frielink & Embregts, 2013).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…This technique is often used in Dutch general dental practice to enhance patients' intrinsic motivation for adhering to oral‐health‐promoting behaviours (Gresnigt‐Bekker, 2011). The OHPs in our study also indicated using this technique, although its effectiveness in oral healthcare has not yet been confirmed (Carra et al, 2020; Gao et al, 2014; Ulliana et al, 2021). In addition, it should be noted that there are various ways in which MI should be tailored to the special needs of those with MBID, such as adapting the language, summarising frequently, and using visual aids and role‐play (Frielink & Embregts, 2013).…”
Section: Discussionmentioning
confidence: 49%
“…has not yet been confirmed (Carra et al, 2020;Gao et al, 2014;Ulliana et al, 2021). In addition, it should be noted that there are various ways in which MI should be tailored to the special needs of those with MBID, such as adapting the language, summarising frequently, and using visual aids and role-play (Frielink & Embregts, 2013) (Smith et al, 2020) as that can also aid implementation researchers and implementation partners in the planning and execution of practice change initiatives.…”
Section: The Role Of Oral Healthcare Professionalsmentioning
confidence: 98%
“…Kemampuan menyikat gigi secara baik dan benar merupakan faktor yang cukup penting untuk pemeliharaan kesehatan gigi dan mulut. Keberhasilan pemeliharaan kesehatan gigi dan mulut juga dipengaruhi oleh faktor penyikatan gigi, serta frekuensi dan waktu penyikatan yang tepat (Ulliana et al, 2021).…”
Section: Kebijakan Permenkes Republik Indonesiaunclassified
“…According to WHO, 60% -90% of school age children experience dental caries. National data in Indonesia reports that the 10-14 year age group has a caries prevalence of 57.6% (Ulliana. et al, 2021).…”
Section: Introductionmentioning
confidence: 99%